Insecticide practice for aphid control in potatoes - van_Toor, R.F.; Teulon, D.A.J. (New Zealand Plant Protection, 2006)
Insecticide use for aphid control in potatoes by mainly Canterbury growers was assessed by a New Zealandwide postal survey in 200102 and by examination of spray diaries from Canterbury (11 seed and 13 process growers) in 200304 Only 22 (16 growers) of seed and 4 (12 growers) of fresh potato growers responded to the postal survey with Canterbury growers making up 93 of the respondents Overall results indicate that most seed crops received a single seed/tuber treatment as well as approximately five foliar applications Most process crops (200304 only) were seed/tuber treated with 0 or 1 foliar applications For fresh crops (200102 only) 59 were seed/tuber treated and 14 had 2 or 6 foliar applications Seed/tuber treatments were mostly imidacloprid but also phorate Foliar applications included organophosphate carbamate synthetic pyrethroid and pyridineazomethine insecticides Insecticide use patterns are discussed in relation to the effectiveness of aphid/virus control and the risk of insecticide resistance